2021
DOI: 10.36740/wlek202108126
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors in the Serum of Patients With Papillary Thyroid Cancer

Abstract: The aim is to study the level of insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-2 (IGF-2) in the blood serum of patients with papillary thyroid cancer, depending on the main clinical and morphological features of the disease. Materials and methods: The material was the information about 60 patients with papillary thyroid cancer (group 1). In group 2 there were 10 patients without oncopathology. All patients underwent clinical examination after total thyroidectomy before special treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Liu et al [50] reported higher IGF-1 and IGF-1R mRNA and protein levels in the thyroid tissues of patients with follicular adenoma, nodular goiter, and papillary thyroid carcinoma than in the controls. Furthermore, a study on serum levels of IGF-1 and insulin-like growth factor-2 (IGF-2) in patients with papillary thyroid carcinoma showed that serum levels of 63% of IGF-1 and 85% of IGF-2 in patients with papillary thyroid carcinoma may be higher than those in controls [51]. Some scholars [52] studied thyrocyte-specific insulin receptor (IR) and IGF-1R double knockout (DTIRKO) mice.…”
Section: Acromegaly Significantly Increases Thyroid Cancer Riskmentioning
confidence: 99%
“…Liu et al [50] reported higher IGF-1 and IGF-1R mRNA and protein levels in the thyroid tissues of patients with follicular adenoma, nodular goiter, and papillary thyroid carcinoma than in the controls. Furthermore, a study on serum levels of IGF-1 and insulin-like growth factor-2 (IGF-2) in patients with papillary thyroid carcinoma showed that serum levels of 63% of IGF-1 and 85% of IGF-2 in patients with papillary thyroid carcinoma may be higher than those in controls [51]. Some scholars [52] studied thyrocyte-specific insulin receptor (IR) and IGF-1R double knockout (DTIRKO) mice.…”
Section: Acromegaly Significantly Increases Thyroid Cancer Riskmentioning
confidence: 99%
“…РЩЖ через сигнальный путь STAT3. Ряд других исследований [15,16] подтверждают, что повышенный уровень ИФР-1 можно расценивать как диагностический и прогностический маркер развития РЩЖ. В ранее проводимых исследованиях мы не выявили оценок корреляции темпа увеличения объема щитовидной железы и риска развития РЩЖ, что может являться одним из маркеров онкотрансформации.…”
Section: а б в гunclassified